An empirical workflow of uncertainty quantification to evaluate agent-based simulation outputs aiming analytical confidence - Abreu, Carolina Gonçalves (2018)
Tese (doutorado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2018.